(untitled) (CIPEEX, 2024)
The objective was to evaluate the influence of abdominal obesity on the emergence of DM2 and AH in a population in the city of Ceres-GO. The studied sample consisted of 75 adult individuals living in the municipality. An anthropometric assessment was carried out using BMI added to WC, classifying high risk of diseases when BMI in both genders > 25.0 kg/m² and WC > 102 cm for men and WC > 88 cm for women. The waist-hip ratio index (WHR) was considered a high risk for the health of men WHR > 0.94 and for women WHR > 0.82. The diagnosis of DM2 was ≥ 110mg/dl, for the diagnosis of AH when values ≥ 130 mmHg or ≥ 85 mmHg. Data from the studied population were previously processed and the individuals were classified and divided according to WHR and BMI/WC combination. Anthropometric analysis of abdominal obesity and its influence on type 2 diabetes mellitus and hypertension in the local population. The indicators of abdominal obesity used in the study, represented by BMI/WC and WHR, showed a strong association with the emergence of AH and DM2. The results demonstrated that there are significant differences for AH, when dividing low-risk and high-risk groups, both using the BMI/CC protocol (0.006); Regarding the WHR protocol (0.0014). In relation to DM2, the results demonstrated a strong relationship with the increase in abdominal obesity and the influence on the increase in fasting blood glucose, both in BMI/WC (0.006*) and also in WHR (0.014*), which confirms the scientific findings who cite the close relationship between increased abdominal adiposity and the secretion of resisting, a small protein that acts on insulin resistance, causing the onset of DM2. This study provides data on the influence of abdominal obesity on AH and DM2 in a rural population in northern Brazil, contributing to raising awareness of the importance of weight control, especially abdominal obesity, in preventing the emergence of these chronic diseases using markers such as WHR and BMI are easy to acquire and very good prediction, in addition to facilitating initial diagnosis, reducing intervention costs.